Clay sediment geopolymerization by means of alkali metal aluminate activation. Issue 130 (18th December 2015) - Peirce, Sara; Santoro, Luciano; Andini, Salvatore; Montagnaro, Fabio; Ferone, Claudio; Cioffi, Raffaele
Abstract : Alkali metal aluminate activation of a lake sediment has proved to be successful for the formation of geopolymer-based materials. Abstract : In this work a clay sediment from a reservoir was employed for the synthesis of geopolymers. The sediment was calcined at 650 and 750 °C for 1 h to ensure the conversion of aluminium coordination from octahedral to tetrahedral. The sediment was characterized by means of X-ray fluorescence, X-ray diffraction, thermogravimetry, mercury intrusion porosimetry and scanning electron microscopy. After calcination, the sediment was submitted to X-ray diffraction, mercury intrusion porosimetry and scanning electron microscopy. Strongly alkaline sodium and potassium aluminate solutions were used to start the polycondensation reaction responsible for geopolymer formation. The initial alkali metal hydroxide concentrations of these solutions were 17, 15 (only Na), 13, 11 and 8.5 M. Polycondensation was carried out at 60 °C for times ranging from 15 min to 28 d. The geopolymer products obtained in all the experimental conditions tested were submitted to the quantitative determination of the extent of polycondensation through mass increase and loss on ignition, as well as to qualitative characterization by means of FT-IR spectroscopy. A reduced set of samples activated with solutions corresponding to initial [NaOH] 13 M and [KOH] 11 M and cured at 60 °C for 3 and 14 d were used for the determination of apparent density and unconfined compressive strength. These samples were also characterized by means of mercury intrusion porosimetry and scanning electron microscopy. The results have indicated that the development of preformed building materials starting from reservoir sediment, although requiring accurate mix design, can be possible by means of alkali metal aluminate activation.